Timelines of History : the ultimate visual guide to the events that shaped the world - Frances, Peter;Guerrero, Angeles Gavira;Mohun, Janet (New York : DK Publishing, 2011)
With easily accessible cross-references that build bite-size pieces of information into a narrative that leads readers back and forth through time, "Timelines of History" makes the past accessible to all families, students, and the general reader.
1. 8 MYA-3000 BCE : Human origins -- 2. 3000-700 BCE : Early civilizations -- 3. 700 BCE-599 CE : The classical age -- 4. 600-1449 : Trade & invention -- 5. 1450-1749 : Reformation & exploration -- 6. 1750-1913 : The age of revolution -- 7. 1914-2011 : Technology & superpowers
Includes index.
Keywords: HISTORICAL CHRONOLOGY